PLATFORMED NOSTALGIA: AUTOMATTIC-ERA TUMBLR AND THE COMMERCIALIZATION OF HISTORICAL SOCIAL MEDIA NOSTALGIA - Hannell, Briony (AoIR Selected Papers of Internet Research, 2026)
This working paper offers a conceptualization of $2 as a social media platform branding strategy that commodifies historical social media nostalgia, in combination with discourses of corporate social responsibility, to (re)gain social acceptance, symbolic value, and desirability amidst a landscape marked by crisis and distrust. I elaborate on this concept through an analysis of Tumblr's marketing and governance to consider how the platform has, since its acquisition by Automattic in 2019, co-opted popular nostalgic discourses about an imagined ‘simpler’ past of social media prior to the ascendancy of Big Tech. I will ask: to what extent, and in what ways, has Tumblr $2 historical social media nostalgia? What contexts and discourses have shaped Tumblr’s courting of historical social media nostalgia? What does this suggest about how the platform wishes to be understood and interpreted within the cultural imaginary?I argue that Tumblr's use of the nostalgic register intensified following Musk’s acquisition of Twitter (now X) in 2022. The platforming of nostalgia has enabled Tumblr to discursively position itself within the cultural imaginary as $2 and as a liberal foil to illiberal competitors like X. Here, Tumblr reconfigures itself as a folk hero (rather than failure) amongst the giants; its obsolescence no longer evaded but celebrated. These discursive interventions allow us to elucidate what Tumblr views, or wants us to view, as its role and influence in social media history, even if this does not necessarily gel with the platform’s internal priorities and policies in practice.